Segmentasi, Target, dan Posisi Produk Bumbu Saus Padang (Studi Kasus pada CV. Samara Micron Saleronell di Kota Bandung) - Sihombing, Zefanya Kalos; Setiawan, Iwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The culinary industry, particularly the food and beverage sector, is a key driver of national economic growth. One of the products in this sector is cooking spices, with CV. Samara Micron Saleronell being one of the producers of Padang sauce spices. However, this new product has not yet reached its sales targets due to marketing challenges. This study aims to formulate the Segmenting, Targeting, and Positioning of the Padang Sauce Spice product by CV. Samara Micron Saleronell. Using a qualitative method and case study approach, the data was analyzed through the STP (Segmenting, Targeting, Positioning) concept. The results show that the selected segment and target are women aged 25-40 years who are married and employed. The chosen positioning highlights the product's health benefits, shorter cooking time, and authentic Nusantara flavor.